Management of the Quality Improvement of Islamic Education at Madrasah Tsanawiyah Fathul Hidayah - Noviyanti, Shobihatul Fitroh; Salas, Muhammad Kamil; Jamilah, Zahrotul; Rikza, M. Alfan; Anand, Amit (Pascasarjana IAIN Kudus, 2025)
This study examines the implementation of Total Quality Management (TQM) at MTs Fathul Hidayah and its impact on improving educational quality. This study addresses the issue of how TQM principles support active student participation and create a democratic and inclusive school environment. This study describes the implementation of TQM at MTs Fathul Hidayah and its contribution to improving educational quality and fostering a participatory school culture. This research uses a library research method to examine the implementation of Total Quality Management (TQM) in Islamic educational institutions, focusing particularly on its application at MTs Fathul Hidayah. The library research method involves systematic exploration and analysis of relevant literature, including books, scientific journals, previous research, and official reports related to TQM, educational quality improvement, student participation, and Islamic school management. The results of the study indicate that the implementation of TQM at MTs Fathul Hidayah involves all school members, including students, as essential stakeholders in the decision-making processes. Students are recognized as primary stakeholders, and their opinions and needs are considered in every school policy. Open communication and intensive interaction between students, teachers, and the school leadership are key characteristics of the implementation of TQM at this institution. TQM implementation enhances educational outcomes and creates a responsive, democratic, and inclusive school environment that continuously adapts to the evolving needs of its community